#TITLE_ALTERNATIVE# - AHMAD NAUFAL (NIM : 12214083), AULIA
An economic costs model for CO2-EOR project constructed in this study can be used to simply calculate investments and operating costs required for a CO2-EOR project. In this study, the costs model is validated with a CO2 pilot injection project pre-feasibility study in South Sumatera. Aside from the model arrangement, technical and economic evaluation of the CO2 pilot injection project in South Sumatera were also provided. The new approach was gathered from CO2-EOR works of literature, such as the U.S. Department of Energy Reports, consulting firm estimates, and industry references. A field model was used to simulate small-scale CO2-EOR flood by utilizing a commercial compositional reservoir simulator. By making the pre-feasibility report as reference values, costs for the CO2 pilot injection project was calculated and the most suited cost model was chosen. Production forecast from reservoir simulation and costs calculated then tabulated under PSC Cost Recovery and PSC Gross Split petroleum agreement to determine the profitability of the project as well as the most sensitive economic parameters. The model constructed yielded a very accurate result, with just 9% difference to the reference feasibility study for its capital expenditure, and 3% difference for its annual operational expenditure. The reservoir simulation from this study concluded the best technical result and confirmed the basic theory of immiscible CO2 flood. This studyÃ‚Â’s economical evaluation determined that for a small-scale CO2-EOR flood, the most profitable gain is when the project economics are tabulated under PSC Gross Split term, and hydrocarbon production will be the most sensitive parameter in all cases if the CO2-EOR project only produced a small amount of hydrocarbon. The novelty of the new economic model is in its practical use for the industry on its pre-feasibility study stage to estimate investments in a CO2-EOR project.